Towards some issues of scientific study of security measures’ problems in Ukrainian prisons - Колб, Олександр Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The paper analyzes the current scientific researches concerning the application of physical effects, special means and weapons to prisoners in prisons of Ukraine and it’s grounded the need of more active investigation of this problem considering the current state of law and order and the safety of all participants and subjects of penal relationships. The associated membership of Ukraine with European Union set for our state the one of new key tasks – to adapt the legislation of our country to the requirements of regulatory legal act of European Union. This approach should be put into practice also in the sphere of execution of criminal sentences in Ukraine. It could be found in particular in the chapter “The objective and the dates for Conception realization” of Conception of the state policy in the sphere of reformation of the State Penitentiary Service of Ukraine approved by the President’s Decree № 631 of November 8, 2012 . This task has special actuality because of a necessity of solving problems and law and order ensuring in penal establishments and juvenile correctional institutions. The practice of application of physical impact, special weapons and arms against convicted persons in penal institutions should be improved because now it not fully correlates with principles of international law so with demands of Art. 3 of the Constitution of Ukraine, according to which person’s safety, his or her life, health, honor, dignity and immunity are among the highest social values. In practice special weapons are often used by penal establishments and juvenile correctional institutions staff disproportionately to situations in penal facilities. These manipulations are often connected with hard consequences for inmates: bodily harms, injuries and even death cases. For example annually at least 10 persons of penal establishments staff are called for criminal liability for excess of powers and three times more people are made responsible for other kinds of amenability. In addition, wrongful use of safety activities and measures for convicted persons destabilizes the law order in certain penal and correctional facilities, complicates the work of institutions’ administrative units, penal staff and law-enforcement authorities, and distracts workers from their service duties for the time of special measures in prisons.